An explanatory theoretical study of the concept of organizational silence accorging - bouakkaz, amina; doubbakh, kouider (Journal of Social Sciences and Humanities, 2024)
This study aimed to explain the phenomenon of organizational silence as one of the organizational variables through MacGregor Douglas theory, which provided explanations for organizational behavior in terms of a set of perceptions and beliefs that are the reason for the spread of several behavioral manifestations that affect the achievement of the goals planned by the organization, and organizational silence is one of these behaviors. In this context, this article came as a theoretical contribution to highlight the importance of identifying the causes of this behavior in order to reach effective mechanisms to mitigate it by addressing the conceptual framework of the variable of organizational silence and presenting its causes, consequences and effects, then mechanisms for confronting it through this theoretical heritage to provide a comprehensive understanding of the variable, then addressing To interpret it according to the proposed theory and finally present a number of suggestions